2013
DOI: 10.1017/s0033822200058021
|View full text |Cite
|
Sign up to set email alerts
|

Life Science Applications Utilizing Radiocarbon Tracing

Abstract: Life science applications utilizing radiocarbon tracing. ABSTRACT. Radiocarbon-based accelerator mass spectrometry (AMS) facilities at Uppsala University include a measurement center for archaeological applications and a separate entity dedicated to life science research. This paper addresses the latter, with the intention of giving an overall description of the biomedical activities at our laboratory, as well as presenting new data. The ultra-small sample preparation method, which can be used down to a few µg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Unlike Khosh et al [14] we have reported that TiH 2 is not necessary for the graphitization process [11,12]. The sealed graphitization tube is inserted in a heater block and the graphitization takes place at 550°C for 6 h.…”
Section: Graphitizationmentioning
confidence: 89%
See 2 more Smart Citations
“…Unlike Khosh et al [14] we have reported that TiH 2 is not necessary for the graphitization process [11,12]. The sealed graphitization tube is inserted in a heater block and the graphitization takes place at 550°C for 6 h.…”
Section: Graphitizationmentioning
confidence: 89%
“…The USS sample preparation method has been reported earlier [11,12] and is therefore only briefly outlined here. The small samples size sample preparation method differs from the standard mg-AMS in a number of ways, some of which are mentioned here.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently we have adopted an alternative sealed tube method for 1 mg carbon sample size, where the zinc reagent is used as sole reduction agent (Zn-method) [9][10][11] and optimized it for the MICADAS AMS instrument (under publication). This alternative method has already been successfully applied and used in other labs for micrograms sample size [12][13][14]. This way the hydrogen is eliminated from the reaction system and the methane formation is prevented.…”
Section: Methodsmentioning
confidence: 99%
“…This volume contains papers that describe specialized approaches to measure samples containing less than 10 μg C [41–44]. We find drying liquid samples in a lyophilizer using an oilless pump works well to minimize sample loss and keep fossil and contemporary backgrounds low.…”
Section: Methodsmentioning
confidence: 99%